Laparoscopic IPAA Is Not Associated With Decreased Rates of Incisional Hernia and Small-Bowel Obstruction When Compared With Open Technique. Issue 3 (March 2015) - Benlice, Cigdem; Stocchi, Luca; Costedio, Meagan; Gorgun, Emre; Hull, Tracy; Kessler, Hermann; Remzi, Feza H.
<x xml:space="preserve">Abstract</x> BACKGROUND: There are scant data on the presumed reduction of small-bowel obstruction and incisional hernia rates associated with laparoscopic IPAA. OBJECTIVE: The aim of this study was to compare long-term outcomes after open vs laparoscopic IPAA based on a previous study from our institution. DESIGN: This was a retrospective cohort study (from January 1992 through December 2007). SETTINGS: The study was conducted in a high-volume, specialized colorectal surgery department. PATIENTS: Patients included those who were enrolled in a previous institutional case-matched (2:1) study that examined 238 open and 119 laparoscopic IPAAs. MAIN OUTCOME MEASURES: Long-term complications, including incisional hernia clinically detected by physician, adhesive small-bowel obstruction requiring hospital admission and surgery, pouch excision, and pouchitis rates, were collected. Laparoscopic abdominal colectomy followed by rectal dissection under direct vision (lower midline or Pfannenstiel incision) and converted cases were analyzed within the laparoscopic group. RESULTS: Groups were comparable with respect to age, sex, BMI, and extent of resection (completion proctectomy vs proctocolectomy), consistent with the original case matching. Mean follow-up was significantly longer in the open group (9.6 vs 8.1 years; p = 0.008). Open and laparoscopic operations were associated with similar incidences of incisional hernia (8.4% vs 5.9%; p = 0.40), small-bowel obstruction requiring hospital admission (26.1% vs 29.4%; p = 0.50), and small-bowel obstruction requiring surgery (8.4% vs 11.8%; p = 0.31). A subgroup analysis comparing 50 patients with laparoscopic rectal dissection versus 69 patients with rectal dissection under direct vision confirmed statistically similar incidences of incisional hernia, hospital admission, and surgery for small-bowel obstruction. LIMITATIONS: This study was limited by its retrospective nature. CONCLUSIONS: Some of the anticipated long-term benefits of laparoscopic IPAA could not be demonstrated in this cohort. The lack of such long-term benefits should be discussed with patients when proposing a laparoscopic approach.